Membangun Literasi Budaya Lokal Kepada Generasi Z Melalui Tradisi Weh-Wehan di Kecamatan Kaliwungu, Kabupaten Kendal. - Viro Dharma Saputra (PRoMEDIA, 2020)
Abstract The purpose of this study is to introduce the local culture in the form of the weh-wehan tradition. The tradition of welcoming the Prophet's birthday and taking place once a year attracts a lot of attention. Many of the Z generation born in the 1995-2010 range were affected by the use of smartphones to access the latest news and did not pay attention to the existing local culture. This influence is great for the threat of cultural literacy transmitted from gen X to generation Z. Aims to know the cultural literacy carried out by generation Z and the impact of this tradition on generation Z. Using descriptive qualitative and snowball sampling, as informants are local figures representing generation x by the Chair of IPNU, and Gen Z was represented by the youth leaders and students. Based on the results obtained that to build local wisdom, can invite generation z to participate together through the weh-wehan tradition which only takes place once a year in the celebration of the Birthday of the Prophet. It aims to introduce cross-cultural culture that must be held fast to the current generation z.Keywords: Cultural Literacy, Weh-wehan, Generation Z, Prophet's Birthday AbstraksiTujuan penelitian ini untuk mengenalkan budaya lokal berupa tradisi weh-wehan. Tradisi yang dilakukan menyambut maulid nabi dan berlangsung setahun sekali banyak menarik perhatian. Banyak generasi Z yang terlahir dalam rentang 1995-2010 terdampak  dari penggunaan smartphone untuk mengakses berita terkini dan tidak memperhatikan kembali budaya lokal yang ada. Pengaruh ini besar bagi terancamnya literasi budaya yang ditularkan dari gen X kepada kaum generasi Z. Bertujuan untuk mengeatahui literasi budaya yang dilakukan oleh generasi Z serta dampak tradisi ini kepada generasi Z. Menggunakan deskriptif kualitatif dan snowball sampling, sebagai informan adalah tokoh setempat mewakili generasi x oleh Ketua IPNU, serta gen Z diwakili oleh ketua karang taruna dan mahasiswa. Berdasar hasil yang didapat bahwa untuk membangun kearifan lokal, dapat mengajak generasi z untuk berpartisipasi bersama melalui tradisi weh-wehan yang hanya berlangsung setahun sekali dalam perayaan Maulid Nabi. Hal ini bertujuan untuk mengenalkan budaya lintas zaman yang harus tetap dipegang teguh hingga generasi z saat ini. Kata Kunci : Literasi Budaya, Weh-wehan, Generasi Z, Maulid Nabi